π | ||
4sin2(x− | )=3 | |
6 |
π | 3 | π | 3 | |||||
sin(x− | )=√ | v sin(x− | )=−√ | |||||
6 | 4 | 6 | 4 |
π | √3 | π | √3 | |||||
sin(x− | )= | v sin(x− | )= − | |||||
6 | 2 | 6 | 2 |
√3 | √3 | |||
sin t = | v sin t = − | |||
2 | 2 |
π | 4π | |||
t= | +2kπ v t= | + 2kπ | ||
3 | 3 |
π | π | π | 4π | |||||
x− | = | +2kπ v x− | = | + 2kπ | ||||
6 | 3 | 6 | 3 |
3π | 9π | |||
x= | +2kπ v x= | + 2kπ | ||
6 | 6 |
π | 3π | |||
x= | +2kπ v x= | = 2kπ | ||
2 | 3 |
√3 | π | 2π | ||||
sint = | ⇒ t = | + 2kπ v t = | + 2kπ | |||
2 | 3 | 3 |
π | π | |||
x=− | +kπ v x= | +kπ | ||
6 | 2 |
9 | 3 | |||
( | ≠ | ) dostaniemy dwa rozwiązania : | ||
6 | 3 |
π | ||
x = | + 2kπ , k ∊ Z | |
2 |
3π | ||
x = | + 2kπ , k ∊ Z | |
2 |
π | ||
x = | + kπ , k ∊ Z | |
2 |
π | √3 | π | √3 | |||||
sin(x− | )= | lub sin(x− | )=− | ⇔ | ||||
6 | 2 | 6 | 2 |
π | π | π | 2π | |||||
(x− | = | +2kπ lub x− | = | +2kπ) | ||||
6 | 3 | 6 | 3 |
π | π | π | 2π | |||||
lub ( x− | =− | +2kπ lub x− | =− | +2kπ)⇔ | ||||
6 | 3 | 6 | 3 |
π | 5π | π | π | |||||
x= | +2kπ lub x= | +2kπ lub x=− | +2kπ lub x=− | +2kπ | ||||
2 | 6 | 6 | 2 |